On the robust adaptive decentralized control of flexible joint robots - Saha K.; Nagraja T. (My University, 2025)
A decentralized robust adaptive controller has been developed for flexible-joint-robots, as an extension of the controller for rigid robots. Simulation results on one link flexible joint robot is presented to illustrate the tracking capability of the developed controller.